A novel cyclic biased agonist of the apelin receptor, MM07, is disease modifying in the rat monocrotaline model of pulmonary arterial hypertension. (1st April 2019) - Yang, Peiran; Read, Cai; Kuc, Rhoda E.; Nyimanu, Duuamene; Williams, Thomas L.; Crosby, Alexi; Buonincontri, Guido; Southwood, Mark; Sawiak, Stephen J.; Glen, Robert C.; Morrell, Nicholas W.; Davenport, Anthony P.; et al.
Abstract : Background and Purpose: Apelin is an endogenous vasodilatory and inotropic peptide that is down‐regulated in human pulmonary arterial hypertension, although the density of the apelin receptor is not significantly attenuated. We hypothesised that a G protein‐biased apelin analogue MM07, which is more stable than the endogenous apelin peptide, may be beneficial in this condition with the advantage of reduced β‐arrestin‐mediated receptor internalisation with chronic use. Experimental Approach: Male Sprague–Dawley rats received either monocrotaline to induce pulmonary arterial hypertension or saline and then daily i.p. injections of either MM07 or saline for 21 days. The extent of disease was assessed by right ventricular catheterisation, cardiac MRI, and histological analysis of the pulmonary vasculature. The effect of MM07 on signalling, proliferation, and apoptosis of human pulmonary artery endothelial cells was investigated. Key Results: MM07 significantly reduced the elevation of right ventricular systolic pressure and hypertrophy induced by monocrotaline. Monocrotaline‐induced changes in cardiac structure and function, including right ventricular end‐systolic and end‐diastolic volumes, ejection fraction, and left ventricular end‐diastolic volume, were attenuated by MM07. MM07 also significantly reduced monocrotaline‐induced muscularisation of small pulmonary blood vessels. MM07 stimulated endothelial NOS phosphorylation and expression, promoted proliferation, and attenuated apoptosis of human pulmonary arterial endothelial cells in vitro. Conclusion and Implications: Our findings suggest that chronic treatment with MM07 is beneficial in this animal model of pulmonary arterial hypertension by addressing disease aetiology. These data support the development of G protein‐biased apelin receptor agonists with improved pharmacokinetic profiles for use in human disease.